Implication of Simulation in Nursing Education: With Reference to Nursing Students in Saudi Arabia - Mawaddah Mohammed Alhwiti,; Mashael Eid Farg Alameani,; Miqradi Mohammad Alabsi,; Gadah Baker Yahya,; Raseel Shuja Alghamdi,; Abeer Mufarh Hassan Wadaani,; Najwa Ali Yahay Alshaharni,; Noorah Saad Alqahtiny,; Atheer Nasser Ali Alqahtani,; Yousef Shatwi Saud Al Yami,; Ghazy Shatwi Saud Almakaeel,; Areej Ahmed Mohammed Ganwi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Existing processes for certifying and accrediting hospitals and other healthcare institutions were used to develop the simulation. But the Carnegie Foundation has also emphasized simulation as a useful teaching tool for nursing students. The training of student nurses presents a challenge to the advancement of nursing practice. The most important tool they bring to the clinical setting during their nursing profession is their education. As a result, the type of nurses they may become is reflected in their academic training. Nurses must be responsible for the results of their care in addition to having the necessary skills to deliver it effectively. This present study evaluates the scenario in terms of nursing students in selected hospitals of KSA. The study takes into account both the primary and secondary data. SPSS Ver. 22.0 was used to get the statistical results.